ON THE BORDERLINES OF SEMIOTICS (OBJECTIVITY VS. SUBJECTIVITY) - Bujar Hoxha (European Scientific Journal, ESJ, 2014)
The present text tries to elaborate some of the theoretical principles which potentially lead towards defining semiotic approaches. My aim is to establish as much as possible clear-cut limits to semiotic theory. Starting from the communicational processes, my aim is to explain encoding external reality intoa new one in the case of the linguistic field, as well as to overcome semiotics' exactness (in the field of arts). The questions to which I try to answer are for instance Saussurian dichotomy (its objectivity and subjectivity nature), and its practical implications to semiotics. I shall as well try to use an example through a semiotics of passions, (through the example of Shakespeare's Romeo and Juliet, and Prokofiev's Romeo and Juliet) as a tool to contributing to the signification process.